Philippine fever - Cook, Bruce R. 1932- (Fort Collins, Colorado Capital Crime Press, 2006)
When an American arms trafficker named Harvey Tucker is murdered in Manila, AFT agent Sam Haine is sent to investigate. Working with the Manila police, Haine finds that Tucker was involved in far more than selling AK-47s.
Subtitle from cover: "a Sam Haine mystery".
Keywords: United States. -- Bureau of Alcohol, Tobacco, and Firearms -- Officials and employees -- Fiction; Manila (Philippines) -- Fiction